الوعى المعلوماتى بين المكتبيين والأكاديميين - هاشم، مود إسطفان; معلوف، ريتا (البوابة العربية للمكتبات والمعلومات, 2019)
يهدف هذا البحث إلى عرض تجربة مؤسسة شمعة في إقامة 10 دورات تدريبية في وعي المعلومات لطلاب الماجستير والدكتوراه في كليات التربية في جامعات حكومية عربية مختلفة، عنوانها "استخدام مصادر المعلومات التربوية". وهو يعرض لتجربة فريدة شملت 7 دول عربية، هي: لبنان والمغرب ومصر والأردن والكويت وسلطنة عمان والإمارات العربية، كانت فرصة لالتماس حاجات الطلاب المعرفية، وتبين ما يمكن لمكتبيين محترفين أن يقدموه من مهارات ومعرفة في سبيل تطوير البحث العلمي. يقرأ البحث محتوى الدورات التدريبية على ضوء الرؤية الجديدة لوعي المعلومات، كما تعرفه الجمعيات العالمية والخبراء في علم المكتبات؛ ويناقش إمكانية إدماج المكتبات والمكتبيين في العملية التعليمية في الجامعات العربية على ضوء التجربة. وقد تبين من خلال التجربة أن التدريب على وعي المعلومات يحتاج إلى تضافر جهود أعضاء هيئات التدريس والمكتبيين، وهو يبرز أهمية دور المكتبيين ويحسن مكانتهم في المؤسسة التعليمية، لكن حواجز نفسية ومؤسساتية في عدد من الجامعات العربية تعيق إدماج المكتبيين في العملية التعليمية؛ كما يشدد على ضرورة التركيز على مهارات استخدام الأدبيات العلمية وتوليفها ومراجعتها لإنتاج معرفة جديدة في برامج وعي المعلومات.
The aim of this research is to present the experience of the Shamaa Foundation in the establishment of 10 training courses in information awareness for students of master's and doctoral degrees in the faculties of education in various Arab government universities, entitled "The use of educational resources". It offers a unique experience in seven Arab countries: Lebanon, Morocco, Egypt, Jordan, Kuwait, Oman and the UAE. It was an opportunity to seek out the students’ needs for knowledge. It also shows what library professionals can offer to develop scientific research. The research examines the content of the training courses in the light of the new vision of information literacy, as defined by global associations and by experts in library science; it discusses the possibility of integrating librarians in the educational process in Arab universities in the light of experience. It shows that training in information literacy needs to combine the efforts of Faculty members and librarians. It highlights the importance of the role of the librarians and improves their position in the educational institution. However, psychological and institutional barriers in several Arab universities hinder the integration of the library staff into the educational process. Information literacy programs should introduce the necessary skills for synthesizing and reviewing scientific literature in order to produce new knowledge.
Keywords: الوعى المعلوماتى -- طلاب الجامعات -- مصادر المعلومات -- الدورات التدريبية -- مؤسسة شمعة